2005
DOI: 10.5380/avs.v10i2.4432
|View full text |Cite
|
Sign up to set email alerts
|

Fatores Ambientais Que Influenciam O Peso À Desmama, Ano E Sobreano Em Bovinos Da Raça Nelore Mocha, No Sudoeste De Mato Grosso Do Sul - Brasil

Abstract: Animais da raça Nelore Mocha, criados em regime de pastagens, na região sudoeste do estado de Mato Grosso do Sul, no período de 27 anos, permitiu a confecção de um banco de dados com 21.919 observações de pesos a desmama (P205), ao ano (P365) e ao sobreano (P550). Estas foram analisadas pelo método dos quadrados mínimos, para verificar a influência dos fatores ambientais sobre as mesmas. O modelo estatístico incluiu os efeitos fixos de ano e mês de nascimento do bezerro, sexo, região e a covariável de idade da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…Average final weight adjusted for 550 days was 354.71 kg, close to that described by Yokoo et al (2010) with 347.14 kg and by Koury Filho et al (2009) who reported 330.91 kg with a mean age of 523.10 days. The weight gain of 124.49 kg in 224 trial days was higher than that found by Conceição et al (2005) who found a gain between 365 and 550 days of age of 83 kg in Polled Nelore raised under pasture conditions. Differences in genetic makeup and management of the animals (nutritional, handling, age at testing, length of evaluation Fig.…”
Section: Resultscontrasting
confidence: 56%
“…Average final weight adjusted for 550 days was 354.71 kg, close to that described by Yokoo et al (2010) with 347.14 kg and by Koury Filho et al (2009) who reported 330.91 kg with a mean age of 523.10 days. The weight gain of 124.49 kg in 224 trial days was higher than that found by Conceição et al (2005) who found a gain between 365 and 550 days of age of 83 kg in Polled Nelore raised under pasture conditions. Differences in genetic makeup and management of the animals (nutritional, handling, age at testing, length of evaluation Fig.…”
Section: Resultscontrasting
confidence: 56%
“…The result obtained for P120 (126 ± 20.11 kg) was similar to those found in the literature for Nelore, 126 ± 20.11 kg by GARNERO et al (2001) and 121 kg by SIQUEIRA et al (2003). The mean value found for P210 (184 ± 29.27 kg) was similar to that found by Conceição et al (2005) and Payá et al (2007) The results observed in this study for the characteristic P365 (238 ± 38.64 kg) has also been similar to those found by Payá et al (2007) For P450, the result (277 ± 46.96 kg) was similar than those found by Siqueira et al (2003) and Sena (2013) The Table 3 shows the estimates of (co) variance components and genetic parameters for growth traits in Nelore Mocho cattle. It resulted that the values of mean, mode and median were similar for all parameters estimated indicating that the posterior marginal distributions tend to a symmetrical distribution.…”
Section: Resultssupporting
confidence: 87%
“…Grecellé et al (2006), observed an increase in the pregnancy rate of beef cows, related to improvements in body condition score. Vieira et al report that cows between their third and eighth delivery had better pregnancy rates, delivery intervals, and weight of calves at weaning; the last variable was also observed in studies of Bocchi et al (2004), Conceição et al (2005) and Souza et al (2004).…”
Section: Resultsmentioning
confidence: 78%